A metal-free approach towards synthesis of β-carboline C1 substituted Pyrido(2, 3-c)carbazole derivatives (nitramarine analogues) through A3-coupling and estimation of their light emitting properties. Issue 47 (20th November 2020) - Singh, Manpreet; Vaishali,; Kumar, Sunit; Jamra, Rahul; Pandey, Satyendra K.; Singh, Virender
Abstract: A simple and efficient metal-free methodology is presented to access fluorescent β-carboline tethered pyrido(2, 3- c )carbazole derivatives (Nitramarine analogues) via A 3 -coupling of 1-formyl-9 H -β-carbolines, 3-amino-9-ethylcarbazole, and terminal alkynes. The advantages of this approach are operationally simple procedure, use of non-toxic and inexpensive catalyst (I2 ), broad substrate scope, and good yields of products. Moreover, these products showed excellent luminescent properties with quantum yield (ΦF ) up to 60%. Graphical abstract: Image 1 Highlights: One-pot metal-free approach. Yield up to 75%. Broad substrate scope. Excellent photophysical properties. Quantum yield up to 60%.